Does financial disclosure influence the value relevance of accounting information? - Shamki, Dhiaa; Abdul Rahman, Azhar (Emerald Group Publishing Limited, 2013)
Purpose– The paper aims to examine the influence of financial disclosure (FD) level and time on the value relevance of earnings, book value, and cash flows relative to three share price proxies, namely average annual share price, annual closing share price, and share price after a three-month period following the financial year-end for Jordanian companies.Design/methodology/approach – The paper employs price model to examine the influence of FD level and time on the value relevance of three accounting variables relative to three share price proxies for 91 Jordanian companies (consisting of 5,460 observations) within 2004-2009.Findings– Relative to three share price proxies, the findings proved that FD level and time have a significant influence on the value relevance of book value, but not for cash flows. Also, FD level and time have a significant influence on the value relevance of earnings relative to annual closing share price, while they are not relative to share price after a three-month period following the financial year-end.FD time has a significant influence on the value relevance of earnings relative to the average annual share price.Annual closing share price is the most reliable in indicating value relevance of accounting information.Originality/value – The paper confirms that there is a shift away from earnings towards book value as the basis for firm valuation.Market participants might be able to conclude the firm value through the value relevance of accounting information influenced by company's FD.